Epigenetic field cancerization in gastrointestinal cancers. Issue 2 (1st June 2016) - Baba, Yoshifumi; Ishimoto, Takatsugu; Kurashige, Junji; Iwatsuki, Masaaki; Sakamoto, Yasuo; Yoshida, Naoya; Watanabe, Masayuki; Baba, Hideo
Highlights: Epigenetic alterations, including aberrant DNA methylation, play an important role in human cancer development. A field for cancerization, or a field defect, is formed by the accumulation of genetic and/or epigenetic alterations in normal-appearing tissues. A better understanding of epigenetic field cancerization may represent a useful translational opportunity for cancer risk assessment and for cancer prevention. Abstract: Epigenetic alterations, including aberrant DNA methylation, play an important role in human cancer development. Importantly, epigenetic alterations are reversible and can be targets for therapy or chemoprevention for various types of human cancers. A field for cancerization, or a field defect, is formed by the accumulation of genetic and/or epigenetic alterations in normal-appearing tissues and can correlate with risk of cancer development. Thus, a better understanding of epigenetic field cancerization may represent a useful translational opportunity for cancer risk assessment, including previous history and exposure to carcinogenic factors, and for cancer prevention. In this article, we summarize current knowledge regarding epigenetic field cancerization and its clinical implications in gastrointestinal cancers, including colorectal cancer, gastric cancer and esophageal cancer.